The medial temporal written word processing system. (October 2019) - Liuzzi, Antonietta Gabriella; Bruffaerts, Rose; Vandenberghe, Rik
Abstract: Traditional neuroanatomical models of written word processing have proposed multiple parallel routes from the visual word form area to lateral temporal, inferior parietal and inferior frontal cortex. Here we hypothesize the existence of an alternative ventromedial occipitotemporal route that culminates in the left perirhinal cortex which codes for the learned association between a concrete written word and the entity it refers to. The hypothesis fits in a broader context that considers perirhinal cortex as a connector hub connecting sensory input with more widespread representations of its content. According to the hypothesis, perirhinal coding of the association between a concrete word and its referent relies on the same operational principles as the coding of paired associates by perirhinal neurons documented by electrophysiological recordings in nonhuman primates. The evidence for a role of human left perirhinal cortex in written word processing is primarily based on two sources: Direct electrophysiological recordings reveal responses to concrete written words compared to function words or nonword stimuli. Secondly, in humans, the conceptual similarity between concrete written words is reflected in the similarity of the activity patterns evoked by these words in perirhinal cortex. The hypothesis has clinical relevance: Patients with the semantic variant of primary progressive aphasia who have damage of the left perirhinal cortex among other anterior temporal regions, have surface alexia as one of their defining features, i.e. the inability to access meaning from written words. The hypothesis of an alternative, ventral occipitotemporal written word processing pathway aligns with the concept that written language processing builds upon pre-existing visual object processing mechanisms.